O impacto dos eventos de vida estressantes em adolescentes com transtorno bipolar - Coelho, Roberta Paula Schell (2012)
The BD with the onset in childhood and adolescence causes considerably serious damages to the emotional growth and development of these individuals. Stressful life events (SLE) have been associated to the appearance of psychopathologies, mainly affective ones, by worsening its prognosis and aggravating the illness course. Although there is scientific relevance in the theme, the studies on juvenile bipolar disorder and life events are scarce in the literature. SLE occurred during childhood and adolescence may be classified as an exposure to a unique or to different situations that cause stress to the organism and exceed the child s or adolescent s capacity to understand and handle such event. For aproximately 40 years, the researches on life events have been focusing their interest in etiological issues about psychiatric morbidity in general, through the understanding of genetic and environmental interactions. However, while verifying the studies from these decades of scientific production, a considerable gap can be noticed, regarding the instruments and assessing measures referring to such events. Studies demonstrate a positive association between the presence of a toxic environment and the neuropsychophysiological vulnerability. Even though many of studies propose to verify the adverse events occurred during life, it is noticed the lack of a consensual instrument in the literature for this measure. The beginning of this work had the purpose to translate and adapt to the Portuguese language an instrument denominate Stressful Life Events Schedule (SLES), that investigates the SLE occurred in adolescents in the last 12 months, in order to strongly implement and support with a greater robustness the studies of this theme. The instrument showed as an useful 9 tool, in an general manner, the items had a good equivalence among the versions. The appreciation of conceptual equivalence and of items enabled linguistic adjustments and terminological adaptations of some terms. Further study is required to evaluate the other psychometric properties of the SLES in our culture. The second article indicated association between the humor symptomatology and global functioning to the SLE occurred in the last year in 23 adolescents with BD and 20 healthy controls without psychopathology. To evaluate the life events it was used the SLES-Adolescents, through having a face to face interview, that is accompanied with a scale having 79 SLE. To verify the severity of impact of these SLE, each item had a four point scale (not at all, a little, somewhat and a lot). This data revealed a frequency of SLE significantly higher in bipolar adolescents than in the healthy controls. Besides that, a positive association between the number of SLE and the seriousness of maniac depressive symptoms, as well as a reduction of the global functioning of individuals with humor disorder was detected. The occurrence of SLE appears associated with maniac and depressive symptoms as well as the reduction of the overall functioning of the individual assailed by bipolar disorder. Finally, this dissertation has the purpose of contributing to an acknowledgment of the psychosocial vulnerability factors associated with bipolar disorder in adolescence.